AN ECOLOGICAL STUDY OF ENDEMIC PLANT POLYGONUM ISTANBULICUM KESKIN AND ITS ENVIRONS - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2013)
In this study, some ecological features of narrow endemic Polygonum istanbulicum Keskin, which was established as a new plant species in 2009, and its environs were examined. There are 41 known Polygonum taxa in Turkey and the genus is represented by 14 species in Istanbul. Plant and soil samples were collected from the place where the species merely lives in the world (Basibuyuk Forest, Maltepe District, Istanbul/Turkey). Plant and soil samples were collected by using standard methods and root, branch, leaf and soil mineral nutrients (Ca, Cu, K, Mg, Mn, N, P, Na, Zn), were measured. Additionally, soil texture, structure and other physical and chemical measurements such as pH, total protein and electrical conductivity (EC) were determined.
Keywords: FE; NI